2019
DOI: 10.1016/j.molmet.2019.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticles inhibit beige fat function and promote adiposity

Abstract: Objective Obesity is a complex chronic disease of high prevalence worldwide. Multiple factors play integral roles in obesity development, with rising interest focusing on the contribution of environmental pollutants frequent in modern society. Silver nanoparticles (AgNPs) are widely used for bactericidal purpose in various applications in daily life. However, their potential toxicity and contribution to the obesity epidemic are not clear. Methods Beige adipocytes are ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 39 publications
(45 reference statements)
1
20
0
Order By: Relevance
“…The 3T3-L1 cells produce large amounts of ROS during differentiation into adipocytes, which promotes intracellular lipid accumulation and inhibits browning gene expression. , Reducing the excess generation of ROS can effectively inhibit fat accumulation in adipocytes and alleviate obesity-associated metabolic disorders. , MnNPs catalyzed the dismutation of superoxide radicals to H 2 O 2 and the subsequent reduction of H 2 O 2 to water by mimicking SOD and CAT, respectively. In this study, the 3T3-L1 cells were treated with SF@Rsg-Mn, SF@Rsg, SF@Mn, or Rsg-Mn during differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…The 3T3-L1 cells produce large amounts of ROS during differentiation into adipocytes, which promotes intracellular lipid accumulation and inhibits browning gene expression. , Reducing the excess generation of ROS can effectively inhibit fat accumulation in adipocytes and alleviate obesity-associated metabolic disorders. , MnNPs catalyzed the dismutation of superoxide radicals to H 2 O 2 and the subsequent reduction of H 2 O 2 to water by mimicking SOD and CAT, respectively. In this study, the 3T3-L1 cells were treated with SF@Rsg-Mn, SF@Rsg, SF@Mn, or Rsg-Mn during differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, the authors [ 65 ] showed that big doses of AgNPs can cause adiposis, with the fat tissue gain rate increasing significantly starting from the seventh day after the AgNPs administration. It might be so that the same effect was observed following the administration of the 4–7.5 mg/kg AgNPs-BAC dose ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…An exploration of the in vivo and in vitro role of silver nanoparticles in thermogenic beige adipocyte differentiation revealed that AgNP inhibited beige adipocyte differentiation, adipocyte thermogenesis, and mitochondrial functioning. AgNP elevated ROS levels within beige adipocytes and activated the MAPK-ERK signaling pathway which is involved in adipogenesis ( 114 ).…”
Section: Metalsmentioning
confidence: 99%